International Law at the Saint Volodymyr Imperial University of Kyiv in the 19th and Early 20th Centurie (Polish Yearbook of International Law, 2021)
This article is devoted to the science of international law at the Saint Volodymyr Imperial University of Kyiv, a major centre for the teaching and study of international law in Tsarist Russia. It examines the international legal views propounded by Vasilii Andreevich Nezabitovskii (1824–1883), Roman Ivanovich Baziner (1841–?), Nikolai Karlovich Rennenkampf (1832–1899), Otton Ottonovich Eikhel’man (1854–1943), and Petr Mikhailovich Bogayevskii (1866–1929). Scientists working at the Saint Volodymyr Imperial University contributed considerably to the development of the science of international law, although their work is not widely known due to the fact they did not produce many works in “western” languages. The large majority of these scholars’ writings represent a perfect development of international legal theory. These works advanced the concepts of the legal nature of international law (Nezabitovskii, Eikhel’man); proposed a new spatial concept of territory that was further developed in international legal science (Nezabitovskii); and explored the laws and customs of war and the role of the Red Cross in the development of humanitarian norms in international law (Baziner, Rennenkampf, Bogayevskii).